Analysis of the Relationship Between Indonesian Language Task Assignment and Student Learning Motivation: A Quantitative Study of Fourth-Grade Elementary School Students - Efrina Hayani; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study aims to analyze and determine the significance of the relationship between giving Indonesian language subject assignments and the level of learning motivation in fourth grade students of State Elementary School 110 Gunungmanaon. The research method used is a quantitative approach with a correlational research design. The population of this study was all fourth grade students of State Elementary School 110 Gunungmanaon, with a research sample of 48 students. The results of the data analysis showed several important findings. First, the quality of giving Indonesian language assignments is in the "good" category with an average indicator score of 47.88. This indicates that the tasks given by the teacher have been carried out quite well and variedly. Second, the level of learning motivation of fourth grade students of SDN 110 Gunungmanaon is included in the "high" category. This indicates a strong drive and enthusiasm for learning in students. Third, the results of the Pearson Product Moment correlation analysis show a strong positive relationship between giving Indonesian language assignments and the level of student learning motivation, with a correlation coefficient value (rₓᵧ) of 0.772. Furthermore, hypothesis testing using a significance test shows that the calculated r (0.772) is greater than the r table (0.284) at a significance level of 5%. Based on these results, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. The conclusion of this study is that there is a significant and strong positive relationship between giving Indonesian language assignments and the level of student learning motivation of fourth grade students of SDN 110 Gunungmanaon. The implication of this study is that effective and varied assignments have a crucial role in fostering and maintaining students' learning motivation.